Secrecy performance analysis with relay selection methods under impact of co‐channel interference. Issue 11 (1st July 2015) - Duy, Tran Trung; Duong, Trung Q.; Thanh, Tu Lam; Bao, Vo Nguyen Quoc
Abstract : In this study, the authors evaluate secrecy performance of cooperative protocols with relay selection methods under impact of co‐channel interference. In particular, the authors propose an optimal selection scheme to maximise the secrecy capacity obtained at the cooperative phase. In addition, the authors also consider suboptimal and random selection schemes which reduce the complexity of implementation, when compared with the optimal one. For performance evaluation, the authors derive exact and asymptotic closed‐form expressions of secrecy outage probability and probability of non‐zero secrecy capacity for the considered schemes over Rayleigh fading channels. Monte Carlo simulations are performed to validate the derivations.